A prospective comparison of dynamic contrast-enhanced MRI and 51Cr-EDTA clearance for glomerular filtration rate measurement in 42 kidney transplant recipients. Issue 117 (August 2019) - Taton, Benjamin; De La Faille, Renaud; Asselineau, Julien; Perez, Paul; Merville, Pierre; Colin, Thierry; Combe, Christian; Sourbron, Steven; Grenier, Nicolas
Abstract: Objectives: To evaluate the performance of dynamic contrast-enhanced MRI measurement of glomerular filtration rate (GFR) compared with the reference standard technique of urinary clearance of 51 Cr-EDTA. Patients and methods: All kidney transplant recipients (KTRs) with an indication for non-urgent contrast-enhanced MRI at our institution were prospectively included between 2008 and 2012. Renographies were acquired by low-dose dynamic contrast-enhanced MRI (DCE-MRI) then fitted with a two-compartment pharmacokinetic model. MR-GFR was compared with reference isotopic measurements using Bland-Altman diagrams, intraclass correlation coefficient (ICC) and concordance rates. Results: Forty-two KTRs (mean age 51.5 years, 26–74) were analyzed. Mean estimated GFR was 48.5 ± 27 mL/min/1.73m 2 (24–178 mL/min). The mean bias was +13.2 mL/min (6.4–20.0, +36.9%) ranging from -31.0 mL/min (-41.7%) to +101.4 mL/min (+89.2%) with a large variability (standard-deviation: 22.3 mL/min; limits of agreement: [-30.6 (-43.3–-18.9); +57.0 (45.3–68.7)]). The ICC was 0.32 (0.02–0.56) and the concordance rate was 28.6% (14.9–42.2). Conclusions: The large variability of MR-GFR compared with the reference technique precludes its use in KTRs, whose anatomical peculiarities make standardization of arterial input function (AIF) difficult.